Remote sensing estimates of the ocean surface partial pressure of CO2 and air-sea CO2 fluxes in the Baltic Sea, 1998-2011 - Rutgersson, Anna; Alexandre Charantonis, Anastase; Parard, Gaelle (Uppsala University, 2019)
Ocean surface partial pressure of CO2 (pCO2) and air-sea CO2 fluxes in the Baltic Sea estimated using self-organizing map classifications along with class-specific linear regressions (SOMLO methodology). The estimates have a spatial resolution of 4-km both in latitude and longitude and a monthly temporal resolution from 1998 to 2011. The CO2 fluxes are estimated using reanalysis winds and the method of Wanninkhof et al. (2013).

For more details see:
Parard, G., Charantonis, A. A., and Rutgerson, A.: Remote sensing the sea surface CO2 of the Baltic Sea using the SOMLO methodology, Biogeosciences, 12, 3369-3384, https://doi.org/10.5194/bg-12-3369-2015, 2015.

Wanninkhof, R., Park, G.-H., Takahashi, T., Sweeney, C., Feely, R., Nojiri, Y., Gruber, N., Doney, S. C., McKinley, G. A., Lenton, A., Le Quéré, C., Heinze, C., Schwinger, J., Graven, H., and Khatiwala, S.: Global ocean carbon uptake: magnitude, variability and trends, Biogeosciences, 10, 1983-2000, https://doi.org/10.5194/bg-10-1983-2013, 2013.

Uppskattningar av partialtryck för koldioxid vid havsytan med hjälp av fjärranalys i Östersjön 1998-2011.

Se engelska katalogsidan för detaljerad information: https://snd.gu.se/en/catalogue/study/ECDS0250
Partialtryck av koldioxid vid havsytan i Östersjön, 1998-2011
Keywords: OCEAN CHEMISTRY; ocean; ocean; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav